Interpretation of Judicial Rulings - Hussien Abd Allah (Journal of Legal Sciences, 2024)
Abstract Judicial rulings are considered procedures for filing a dispute before the judiciary, as the issuance of a judicial ruling ends the dispute and resolves the conflict. Therefore, the judicial ruling must be clear, free of ambiguity or vagueness, and does not raise confusion. Any ambiguity or vagueness that affects the judicial ruling makes its application impossible. Therefore, the legislator made the way to interpret ambiguous judicial rulings a way for the litigants or those executing those rulings to resort to the court that issued them to clarify the ambiguity or vagueness surrounding its ruling, so that the party executing these rulings can implement it according to its content and grant the opponents their rights. Therefore, this research came to explain the concept of interpreting a judicial ruling and then explaining the conditions for interpreting a judicial ruling and the court competent to interpret the ruling and its discretionary authority.